EXPERIMENTAL STUDY OF CARBON MEDIA VARIATIONS SEM TEST AND TEMPERATURE ON STAINLESS STEEL 316L PACK CARBURIZING COATING ON THERMAL CONDUCTIVITY AND CORROSION RATE - Reinardi Odilian Jahu; Nereus Tugur Redationo; Bernardus Crisanto Putra Mbulu (Universitas Katolik Widya Karya Malang, 2026)
This study analyzed the characteristics of carbon produced from coconut shells and Arabica coffee grounds through a pyrolysis process at a temperature of 1000°C for 1 hour. The SEM test results showed that coconut shells contained 91.87% carbon, while Arabica coffee grounds contained 74.39% carbon, indicating a higher carbon content in coconut shells. Furthermore, this study evaluated the effect of coconut shell carbon and Arabica coffee grounds carbon with temperature variations on the thermal conductivity and corrosion rate of 316L stainless steel plates. The results of the study showed that the highest thermal conductivity values ​​for coconut shell carbon and Arabica coffee grounds were 19.06087 W/m°C and 18.959905 W/m°C, respectively, both achieved at a temperature of 900°C. Increasing the temperature in the pack carburizing process significantly increased the carbon content in 316L stainless steel, which had a positive impact on increasing thermal conductivity. Coconut shell carbon at 900°C showed the lowest corrosion rate of 4.35 mm/year, while Arabica coffee grounds carbon at the same temperature had a corrosion rate of 5.81 mm/year. In conclusion, the effect of adding carbon with temperature variations in the pack carburizing process can increase hardness. The corrosion rate on 316L stainless steel plate will be lower because it contains Cr, Ni, and C which affect strength and high temperature resistance, especially hardness.